Coronary Artery Z-scores in Febrile Children with Suspected Kawasaki's Disease—The Value of Serial Echocardiography - Gerling, Stephan; Hörl, Maria; Geis, Tobias; Zant, Robert; Dechant, Markus-Johann; Melter, Michael; Michel, Holger (The Thoracic and Cardiovascular Surgeon, 2022)
Background Progressive enlargement of the coronary artery (CA) diameters on serial echocardiography can support diagnosis of Kawasaki's disease (KD) even CA dimensions are within the normal range.Methods A single-center, retrospective study compared mean Z-scores of the proximal CA internal diameters in children hospitalized with non-KD febrile illnesses (FCs) with those of KD patients.Results A total of 223 patients with suspicion of KD have been admitted over a period of 16 years and data were evaluable for 176 children. Distributions for age, sex, and body surface area were similar for both groups. FC had a significantly shorter duration of hospitalization, higher levels of hemoglobin, lower levels of liver transaminases, and segmented neutrophils, respectively. The majority of FC patients (75/82, 91.5%) had normal CA Z-scores (p < 0.001) and only 3 (3.7%) had CA Z-score ≥2.5 standard deviation (SD). In KD, subjects (46/94, 49.5%) had a CA dilation (Z-score ≥2.5 SD) and the maximum CA Z-score (Zmax) was significantly higher compared with FC patients (p < 0.001). On serial echocardiograms, FC patients showed a mild decrease, whereas KD patients developed a significant increase of CA Zmax (p < 0.001). Seven KD patients had a segmental dilation of a CA which has been confirmed by cardiac catheter. In FC, no segmental dilation of any CA was documented by echocardiography.Conclusion This study found that mean CA dimensions in FCs were smaller and did not increase in serial echocardiograms compared with KD patients.
Keywords: Kawasaki's disease; aneurysm; coronary artery; serial echocardiography; Z-scores; febrile children